(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research examines the issue of third-party countermeasures, which has been a subject of doctrinal controversy for a quarter century since the adoption of the articles on the responsibility of states for internationally wrongful acts. The study aims to determine the extent to which unilateral international economic sanctions can be justified on the basis of third-party countermeasures, given the ambiguity surrounding the conduct of states imposing such sanctions. This ambiguity arises from their failure to explicitly state that they are acting on the basis of such countermeasures, while simultaneously declaring that they are acting in response to breaches of obligations erga omnes, and describing these sanctions as a legitimate instrument of foreign policy. By analyzing a number of international practices in this regard—considering relevant international charters, resolutions, and the jurisprudence of the International Court of Justice—it becomes evident that these practices do not satisfy several of the required conditions for countermeasures. This explains why those states refrain from relying on third-party countermeasures to justify such sanctions, and also reveals the shortcomings of the current international legal framework in this area, as well as the need for its further development.